Optical properties of ZnO aggregates in KBr matrix - Samah, M.; Bouguerra, M.; Khelfane, H. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Zinc oxide nanocrystals were prepared, using Czochralski method of growth, in KBr matrix during pulling. Good evidences can prove that the quantum confinement effect is the special quality for this nanosystem. As an indication of quantum confinement effect, excellent emissions from band edge have been observed in optical absorption spectra and on selective PL ones. CL spectrum exhibits several levels in band gap allotted to different types of impurities in matrix and within ZnO aggregates.